2021
DOI: 10.1093/pubmed/fdab007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of vaccine hesitancy in an urbanized agglomeration of New Delhi, India

Abstract: Background The immunization program has been an important part of Indian public health policy for three decades; yet only 62% of children are being fully immunized. Vaccine hesitancy is a major contributor to the immunization gap that needs to be addressed. Methods A cross-sectional descriptive study of prevalence and predictors of vaccine hesitancy was conducted in 350 households having at least one child in the age group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In a cross-sectional study conducted among Italian parent's attitudes on their children's vaccination, 24.6% reported refusing or delayed taking at least one dose of vaccine for their child [ 9 ]. A recent study from New Delhi, India, had found the prevalence of COVID-19 vaccine hesitancy was 28.9% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study conducted among Italian parent's attitudes on their children's vaccination, 24.6% reported refusing or delayed taking at least one dose of vaccine for their child [ 9 ]. A recent study from New Delhi, India, had found the prevalence of COVID-19 vaccine hesitancy was 28.9% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study are nearly similar to studies conducted in West Bengal (29.26%) and New Delhi (28.90). [ 22 25 ] In contrast, a global survey of vaccine hesitancy revealed a 12.5% of prevalence in India. [ 26 ] Also, a few studies conducted in Madhya Pradesh (19.7%), Karnataka (3.40%), Chandigarh (10.00), and Odisha (26.54%) revealed a low prevalence rate compared to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are nearly similar to the results of studies conducted in West Bengal and New Delhi. [ 22 25 ] There was a significant association between literacy and vaccine hesitancy. In the current study, mothers with primary and middle-class education levels and illiterates showed high vaccine hesitancy with P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidry et al found that insurance, education, susceptibility to COVID-19, vaccine benefits, scores of vaccine barriers, subjective norms scores, attitudes towards the vaccine and self-efficacy were significant predictors of COVID-19 vaccination intentions [3]. Meanwhile, concerns about the hasty development of the COVID-19 vaccine [3], fear of needles, concerns about pain during vaccination, lack of family support and concerns about side effects were identified as the reasons for vaccination hesitation [4]. A cross-sectional study in China found that a high perception of the benefits and low perceived barriers to vaccination were the two most important factors influencing a clear intention to vaccinate with COVID-19 [5].…”
Section: Introductionmentioning
confidence: 99%